2009
DOI: 10.1016/j.neuron.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Rewards Evoke Learning of Unconsciously Processed Visual Stimuli in Adult Humans

Abstract: Summary The study of human learning is complicated by the myriad of processing elements involved in conducting any behavioural task. In the case of visual perceptual learning there has been significant controversy regarding the task-processes that guide the formation of this learning, however, there is a developing consensus that top-down, task-related factors, are required for such learning to take place. Here we challenge this idea by use of a novel procedure in which human participants, who were deprived of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
332
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(358 citation statements)
references
References 59 publications
(85 reference statements)
23
332
2
1
Order By: Relevance
“…This enhanced distraction was more evident on trials where spatial attention was directed by competing valid cues. On the other hand, many studies already reported a strong influence of stimuli with emotional significance that are not perceived consciously to induce behavioral and neurophysiological responses (Seitz et al, 2009;Vuilleumier, 2005). Therefore, is explicit knowledge of contingency required for reward learning to occur?…”
Section: Does Motivational Attention Require Consciousness?mentioning
confidence: 99%
See 1 more Smart Citation
“…This enhanced distraction was more evident on trials where spatial attention was directed by competing valid cues. On the other hand, many studies already reported a strong influence of stimuli with emotional significance that are not perceived consciously to induce behavioral and neurophysiological responses (Seitz et al, 2009;Vuilleumier, 2005). Therefore, is explicit knowledge of contingency required for reward learning to occur?…”
Section: Does Motivational Attention Require Consciousness?mentioning
confidence: 99%
“…Therefore, is explicit knowledge of contingency required for reward learning to occur? Seitz et al (2009) studied whether awareness is necessary for the formation of perceptual learning during conditioning. Participants were deprived of food and water, and passively viewed gratings while receiving occasional drops of water as rewards.…”
Section: Does Motivational Attention Require Consciousness?mentioning
confidence: 99%
“…The typical distinction between primary and secondary rewards is that whereas secondary rewards like money or power acquire value or significance only through experiences and associative learning, primary rewards like food and odors have an innate value and biological significance (Gottfried, 2011). Although several studies revealed that primary rewards modify human's perceptual processes (e.g., Seitz, Kim, & Watanabe, 2009) they have never been used, to the best of our knowledge, to investigate attention toward reward-associated stimuli. There are two main advantages in using a primary reward in this particular context.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that these are not the only influences on attentional deployment. To promote survival and well-being, the brain is optimized to learn about perceptual stimuli that signal the potential for procuring reward (7,8). Voluntary attention to stimuli that predict reward is an effective mechanism for efficiently selecting valuable stimuli (9).…”
mentioning
confidence: 99%